Governing the Sun: The Challenges of Geoengineering. Issue 2 (1st December 2019) - Radunsky, Klaus; Cadman, Tim
Abstract: Governments have previously sought to reduce climate-change-inducing concentrations of carbon dioxide in the earth's atmosphere through mitigation and adaptation activities, with limited success. New approaches are being explored, such as negative emissions technologies, including carbon dioxide removal, as well as solar geoengineering, also known as solar radiation management, or modification. This article outlines these emerging technologies focusing on bioenergy, carbon capture and storage, and stratospheric aerosol injection, and explores some of the challenges they pose. Prevention of emissions and their reliable, safe, and environmentally benign removal remain the best options. Robust governance systems and a careful, unbiased, and knowledge-driven assessment of the risks of these emerging technologies are required before they are implemented any further.